Persistence and practice of trading networks a case study of the cereal trade in Mali. (July 2019) - Mangnus, Ellen; Vellema, Sietze
Highlights: A traders 'network is a confederation of skilful people that unite and coordinate a variety of tasks. Functional properties of traders' networks emerge from situated practices and are difficult to design a-priori. A traders' network guarantees its own continuity by opening space for personal skills development of its members. Selection of skilful members is vital for performance and sustenance of a traders 'network. There is a tension between inclusive organisations and the exclusive nature of networks that are able to persistent in the altering realities of trading.